Development of a nucleoside-modified mRNA vaccine against clade 2.3.4.4b H5 highly pathogenic avian influenza virus - Furey, Colleen; Scher, Gabrielle; Ye, Naiqing; Kercher, Lisa; DeBeauchamp, Jennifer; Crumpton, Jeri Carol; Jeevan, Trushar; Patton, Christopher; Franks, John; Rubrum, Adam; Alameh, Mohamad-Gabriel; Fan, Steven H. Y.; et al. (Nature communications, 2024)
mRNA lipid nanoparticle (LNP) vaccines would be useful during an influenza virus pandemic since they can be produced rapidly and do not require the generation of egg-adapted vaccine seed stocks. Highly pathogenic avian influenza viruses from H5 clade 2.3.4.4b are circulating at unprecedently high levels in wild and domestic birds and have the potential to adapt to humans. Here, we generate an mRNA lipid nanoparticle (LNP) vaccine encoding the hemagglutinin (HA) glycoprotein from a clade 2.3.4.4b H5 isolate. The H5 mRNA-LNP vaccine elicits strong T cell and antibody responses in female mice, including neutralizing antibodies and broadly-reactive anti-HA stalk antibodies. The H5 mRNA-LNP vaccine elicits antibodies at similar levels compared to whole inactivated vaccines in female mice with and without prior H1N1 exposures. Finally, we find that the H5 mRNA-LNP vaccine is immunogenic in male ferrets and prevents morbidity and mortality of animals following 2.3.4.4b H5N1 challenge. Together, our data demonstrate that a monovalent mRNA-LNP vaccine expressing 2.3.4.4b H5 is immunogenic and protective in pre-clinical animal models. Highly pathogenic avian influenza viruses from H5 clade 2.3.4.4b are circulating widely in birds and have recently caused large outbreaks in mammals. Here, Furey et al. develop a clade 2.3.4.4b HA-expressing mRNA-LNP vaccine and show that it elicits strong protective immune responses in mice and ferrets.